1996
DOI: 10.1007/bf02254653
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polyester resins with active mineral fillers

Abstract: The technological and operational properties of polyester resins, unmodified and modified with new freely disperse fillers, were investigated. It was found that modification causes greater dependence of the viscosity on the fatigue load and acceleration of the curing reaction and an increase in the exothermic effect by 2.5-4.5 times. In addition, the strength properties of the modified composites and the water and chemical resistance and impact strength are increased. These finely disperse modifiers are of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Since the failure of the adhesive structure also occurs through cracking of the filler particles, and its particles are hollow, it can be concluded that to some extent the filler leads to a decrease in the adhesive strength, which was confirmed by the results of static strength tests. These types of fillers with particle sizes in the order of 10 -6 m usually have a negative effect on the strength of the joints [38][39], but are nevertheless used due to other desirable properties, such as reduction of joint mass, electrical and thermal conductivity of the joint, etc. The adhesive with mineral filler used in the work is usually used where a thick layer of the joint is required or as a putty to fill in unevenness, therefore it is important that its mass is as low as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Since the failure of the adhesive structure also occurs through cracking of the filler particles, and its particles are hollow, it can be concluded that to some extent the filler leads to a decrease in the adhesive strength, which was confirmed by the results of static strength tests. These types of fillers with particle sizes in the order of 10 -6 m usually have a negative effect on the strength of the joints [38][39], but are nevertheless used due to other desirable properties, such as reduction of joint mass, electrical and thermal conductivity of the joint, etc. The adhesive with mineral filler used in the work is usually used where a thick layer of the joint is required or as a putty to fill in unevenness, therefore it is important that its mass is as low as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial thermosetting resins are commonly used with fillers, such as unsaturated polyester resins [28], as a neat [29] and also reinforced by fibers [30]. Murafa et al, [31] stated that this unsaturated polyester resin is typically used to be filled with similar and different materials such as iron, wood, plastics, non-metals or even ceramics. Reduction of surface size occurs at room temperature by curing process.…”
Section: Ocena Wpływu Caco 3 Na Pełzanie Przy Zginaniu Otrzymanego W mentioning
confidence: 99%
“…At the definite amount of filler, the increase of storage module was inversely proportional to the size of filling material [39]. The composite with finely dispersed fillers increase the strength and density, while decreasing the water absorption [40].…”
Section: Particle Size Distribution Of Cacomentioning
confidence: 99%